OUT IN SPACE: Difference and Abstraction in Planetary Urbanization. (8th May 2020) - Angelo, Hillary; Goh, Kian
Abstract: A common thread has emerged in recent critiques of planetary urbanization. Whether on empirical, epistemological or theoretical grounds, critics tend to posit 'difference against abstraction', arguing that planetary urbanization—as an abstract theory of large‐scale phenomena—occludes 'everyday' embodied, small‐scale and place‐based forms of social difference in its production and/or application. Here we engage with this critique as two queer, feminist scholars sympathetic both to critics' arguments about the politics of knowledge production and to the planetary urbanization framework. While we agree that the theory's most visible adherents have not systematically engaged with questions of difference, especially at smaller scales of social analysis, we reject the suggestion that planetary urbanization is inherently incompatible with such concerns. Rather, we argue that the opposite is true. Using examples from our own research, we show how the planetary urbanization framework—by enforcing a multiscalar and non‐city‐centric view of apparently local phenomena—can be central to theorizing and understanding social difference at the level of everyday life in empirical research.